New TOEIC writing coach (Tổng hợp Thành phố Hồ Chí Minh, 2011)
Contents: A full coverage of all question types and tasks of the TOEIC Writing test to familiarize you with the test items. Samples are carefully selected to reflect the real-test task variety as well as difficulty.; A full analysis of successful and unsuccessful answer to help you identify possible problemactic and make progress in a most effective manner; A full practice test to apply what you have studied and monitor your progress